Ischemic Colitis after Colonoscopy with Bisacodyl Bowel Preparation: A Report of Two Cases. (26th November 2020) - Shamatutu, Chris; Chahal, Daljeet; Tai, Isabella T.; Kwan, Peter
Abstract : Background . Colonoscopy is widely used for the diagnosis and management of colorectal disease and requires adequate bowel preparation. Ischemic colitis is a form of intestinal ischemia that presents with abdominal pain, diarrhea, and hematochezia. Risk factors include advanced age, cardiovascular disease, and diabetes. Both colonoscopy and bisacodyl bowel preparation have been described as rare causes of ischemic colitis with less than 35 cases collectively in the literature. Our review found that of these cases, there exists significant heterogeneity within individual patient characteristics. The majority of the cases are managed conservatively without complications or sequela. Due to the risk of ischemic colitis, the FDA has withdrawn bisacodyl bowel preparations from use in the USA. Bisacodyl bowel preparations are still used in Canada. Cases . Here, we present two cases of ischemic colitis in previously healthy women aged 57 and 69 who underwent screening colonoscopy using bisacodyl bowel preparation. Both were treated conservatively without complications. Conclusion . Thus far, there has been one documented case of ischemic colitis following colonoscopy with bisacodyl bowel preparation; here, we present two additional cases with one case occurring without the presence of known risk factors for ischemic colitis. Our literature review finds that there is limited evidence surrounding bisacodyl as a causative agent of ischemic colitis. Cases often contain confounding variables such as the presence of known risk factors for ischemic colitis. Our report aims to highlight the need for a more comprehensive analysis evaluating the safety of bowel preparations as well as increasing the clinical awareness surrounding the rare risk of colonoscopy-induced ischemic colitis.